Layers of Class Distinction in Annie Ernaux’s A Woman’s Story: A Bourdieusian Analysis - Dhakal, Alina (SCHOLARS: Journal of Arts & Humanities, 2025)
This study explores the multifaceted portrayal of class in Annie Ernaux’s autosociobiographical narrative A Woman’s Story, focusing on both visible and invisible layers of class distinction. The research problem stems from Ernaux’s own witness to class distinction at first within her family; between her father’s modest working-class values and her mother’s aspirational bourgeois outlook and later, within herself; between her roots and the elite world she enters through education. These personal contradictions disrupt the simplistic view of class as purely economic, instead calling for a deeper psychosocial investigation. The study delves into the apparent class distinction through the depiction of three generations: her grandparents, parents and Ernaux’s own. It explores that after their social ascent to middle class, her father clings to working-class origin but her mother wants to learn and implement bourgeoisie’s norms, values and cultures to keep up one’s position. Not only in terms of their contrasting tastes, but class distinction also becomes more apparent in their markedly different lifestyle choices, usage of languages and manners they exhibit. Moreover, the study investigates how class distinction operates at the deeper psychological level of the class immigrants through their deeply internalized experiences of humiliation, inferiority and social dislocation. Furthermore, situating itself within the broader framework of social theory of Pierre Bourdieu, this study concludes that A Woman’s Story exposes class distinction as a psychological and symbolic burden, not merely economic condition.